Schematic Visual Representation of Exponentiation - Darja Antolin; Urška Lipovec (University of Maribor Press, 2015)
Visualization of mathematical concepts is an effective learning and teaching strategy. Within mathematics lessons, visualisation is mostly present at iconic level, where concepts are graphically represented. In this paper we present the study that aimed at investigating the presence of schematic visual representation of exponentiation 2³ among pupils attending gymnasium and students, future elementary teachers and future teachers of mathematics (N = 483). Our findings show that schematic visual representation appeared only in little more than a third of all drawings. Additionally, we observe that participants are much more oriented to representing the result rather than the concept. At the end, we add methodical guidance on introducing the concept of exponent through the structure of nested fission, which leads to more conceptual understanding of this elementary mathematical concept.